Captain America. The first avenger [videorecording (Blu-Ray)] - Evans, Chris, 1981-; Atwell, Hayley, 1982-; Weaving, Hugo, 1960-; Stan, Sebastian, 1982-; Jones, Tommy Lee, 1946-; Jackson, Samuel L. (Marvel cinematic universe., 2017)
Captain America leads the fight for freedom in the action-packed blockbuster starring Chris Evans as the ultimate weapon against evil! When a terrifying force threatens everyone across the globe, the world's greatest soldier wages war on the evil HYDRA organization, led by the villainous Red Skull.--From container.